2008
DOI: 10.1037/0022-3514.94.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of self-regulation: How (un)accomplished goal actions affect motivation.

Abstract: Two factors increase the motivation to adhere to a goal: goal commitment and lack of goal progress. When people ask about commitment, focusing on what they have accomplished (to date) signals to them high commitment and increases motivation. Conversely, when commitment is certain and people ask about goal progress, focusing on what they have yet to accomplish (to go) signals to them lack of progress and increases motivation. Accordingly, 4 studies show that emphasizing to-date information increases goal adhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
197
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 244 publications
(217 citation statements)
references
References 51 publications
12
197
1
Order By: Relevance
“…That the last contrast was not statistically reliable may have been because we included only regular donors to Compassion at large, whose a priori group identification was relatively high, which limited our ability to effectively induce low identification with the victims. Indeed, previous research categorizes regular donors as having high commitment to a charity goal (Koo & Fishbach, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…That the last contrast was not statistically reliable may have been because we included only regular donors to Compassion at large, whose a priori group identification was relatively high, which limited our ability to effectively induce low identification with the victims. Indeed, previous research categorizes regular donors as having high commitment to a charity goal (Koo & Fishbach, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…However, other factors may also contribute to the small-area effect. In particular, research on the dynamics of self-regulation attests that people obtain different information from completed versus remaining actions (Fishbach, Zhang, and Koo 2009;Koo and Fishbach 2008). Completed actions serve as a signal of personal commitment and increase motivation for those who are not yet committed to their goals, whereas remaining actions signal a need to progress and increase motivation for those who are already committed to their goals.…”
Section: Discussionmentioning
confidence: 99%
“…4). This control condition enabled us to maintain progress information while eliminating the emphasis on completed or remaining actions (see Koo and Fishbach 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice stimuli for this study were identical to study 1 except that after the choice process was complete, participants indicated on 7-point scales how important eating healthy food and eating tasty food were to them personally (1 p not at all important; 7 p extremely important). Since consumers who are chronically conflicted tend to report the conflicting goals as equally important (see Koo and Fishbach 2008, study 1), we use differences in self-reported goal importance as a proxy for chronic conflict between the two competing goals in this study.…”
Section: Methodsmentioning
confidence: 99%